TITIK TEMU ALIRAN FILSAFAT PROGRESSIVE DAN FILSAFAT PENDIDIKAN ISLAM - Nur Effendi, Muhammad; Yusuf, Muhammad (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2024)
The meeting point of Progressive and Islamic educational philosophy is that basically progressivism with Islamic educational philosophy there are similarities and differences, namely that the values of progressivism education have many similarities with Islamic education. Among them is the concept of progressivism education highly values the position of man, and in Islam also man is highly valued. Appreciation for the use of resourcefulness in education is also the same characteristic. Likewise, respect for human freedom in developing all its human potential is also a similarity with Islamic education. While the very basic differences between progressivism education and Islamic education include philosophical foundations that are built both regarding ontology, epistemology and axiology, as well as about the values built and the purpose of education. Islamic education is based on the philosophy of Islamic education derived from the Qur'an and Hadith. The ontological view of Islamic education is focused on the nature of man, nature and God.